Factors influencing the customer intention in adopting autonomous vehicles (AVS) - Chye, Chi Ern (2024)
The research is developed to investigate the factors influencing the customer intention in adopting the autonomous vehicles. The main concern of this research will be around the determine factors includes perceived usefulness, ease of use, safety perceptions, trialability, and price influencing attitudes and behavioral intention to use the autonomous vehicles. There are six hypotheses constructed in order to study and generate comprehensive result.